In Vivo Targeting of Inflammation-Associated Myeloid-Related Protein 8/14 Via Gadolinium Immunonanoparticles - Maiseyeu, Andrei (2012)
OBJECTIVE: Myeloid-related protein (Mrp) 8/14 complex (is a highly expressed extracellularly secreted protein, implicated in atherosclerosis. In this study, we evaluated the feasibility of targeting Mrp in vivo through synthetic immunonanoprobes. METHODS AND RESULTS: Anti-Mrp-14 and nonspecific IgG-conjugated gadolinium nanoprobes (aMrp-) were synthesized and characterized. Pharmacokinetics and vascular targeting via MRI of the formulations were assessed in vivo in high fat-fed apolipoprotein E deficient (ApoE(−/−)), ApoE(−/−)/Mrp14(−/−) (double knockout) and chow-fed wild-type (C57BL/6) mice. Bone marrow-derived myeloid progenitor cells were isolated from both ApoE(−/−) and double knockout mice, differentiated to macrophages, and were treated with LPS, with or without Mrp8, Mrp14, or Mrp8/14; conditioned media was used for in vitro studies. Mrp-activated cells secreted significant amounts of proinflammatory cytokines, which was abolished by pretreatment with aMrp-NP. We show in vitro that aMrp-NP binds endothelial cells previously treated with conditioned media containing Mrp8/14. MRI following intravenous delivery of aMrp-NP revealed prolonged and substantial delineation of plaque in ApoE(−/−) but not double knockout or wild-type animals. Nonspecific IgG-conjugated gadolinium nanoprobe-injected animals in all groups did not show vessel wall enhancement. Flow-cytometric analysis of aortic digesta revealed that aMrp-NP present in Ly-6G(+), CD11b(+), CD11c(+), and CD31(+) cells in ApoE(−/−) but not in double knockout animals. CONCLUSION: Targeted imaging with aMrp-NP demonstrates enhancement of plaque with binding to inflammatory cells and reduction in inflammation. This strategy has promise as a theranostic approach for atherosclerosis.